2008
DOI: 10.1159/000124850
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Sialic Acid with Markers of Inflammation, Atherosclerosis and Cardiovascular Events in Hemodialysis Patients

Abstract: Background: Serum total sialic acid (S-TSA) is associated with atherosclerotic process in general population. The aim of our study was to evaluate possible correlations of S-TSA with markers of inflammation and atherosclerosis in hemodialysis (HD) patients. Methods: We involved 53 asymptomatic, nondiabetic HD patients and 28 healthy controls. Atherosclerosis was evaluated by carotid ultrasonography, estimating intima media wall thickness and wall to lumen ratio bilaterally. To confirm our findings, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Serum and urinary levels of N ‐acetylneuraminic acid were elevated in individuals suffering from renal failure (Szprynger et al, ). In addition, serum sialic acid was correlated with inflammation and cardiovascular events in patients with renal failure (Tseke et al, ). The significant reversal in the regulation of α ‐CEHC and N ‐acetylneuraminic acid levels in present study may also be attributed to the protective effect of the SA capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and urinary levels of N ‐acetylneuraminic acid were elevated in individuals suffering from renal failure (Szprynger et al, ). In addition, serum sialic acid was correlated with inflammation and cardiovascular events in patients with renal failure (Tseke et al, ). The significant reversal in the regulation of α ‐CEHC and N ‐acetylneuraminic acid levels in present study may also be attributed to the protective effect of the SA capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis showed that serum SA level was closely related with SBP and DBP. Three mechanisms may be involved in the influence of blood SA levels on blood pressure [26,27]. Firstly, SA can promote atherosclerosis development by the inflammatory response, interfere with iron metabolism, and promote platelet thrombus formation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies in hemodialysis patients have demonstrated that the activity of the acutephase response is an important predictor of low serum albumin, and nutritional deficiencies play an important role in endothelial dysfunction, providing a link between malnutrition, inflammation, atherogenesis and excessive cardiovascular morbidity and mortality in hemodialysis patients [23,24] . However, in the present study, no significant association was observed between the C-reactive protein and serum prealbumin level, and C-reactive protein was also not correlated with CA-IMT changes in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%